Determining the effects of the COVID-19 crisis on the human resource management in organizations - Eftimov, Lјupcho; Kamenjarska, Tanja (Published by the Association of Economists and Managers of the Balkans, Belgrade, Serbia, 2021)
Human resource management (HRM), as a crucial constituent of crisis management, has paramount importance in managing the employees and ensuring business continuity, especially during the COVID-19 pandemic. In the constellation of such circumstances, this paper aims to identify the impact of COVID-19 on the HRM in organizations and provide recommendations for the development of long-term strategies, effective management practices and activities that are expected to result in increased employee satisfaction and retention as an organizational response to the crisis. Considering the dynamics and ever-changing environment dominantly, this paper attempts to contribute and expand the HRM literature by providing a comprehensive overview of the level of resilience of HR managers in North Macedonia to deal with a crisis such as the COVID-19 pandemic, and valuable insight into the adequacy of the measures taken. As for the purpose of determining the impact of the crisis on the HRM practices, a structured questionnaire was developed and distributed to the top and middle management, HR professionals and employees in selected companies in the Republic of North Macedonia. The results revealed that adequate managerial responses to the crisis positively influence the organizational performance of the observed companies.
Keywords: COVID-19, Human resource management implications, Organizational response, Crisis management, Employee retention.